Peregrine breathers as design waves for wave-structure interaction. (1st December 2016) - Klein, Marco; Clauss, Günther F.; Rajendran, Suresh; Guedes Soares, Carlos; Onorato, Miguel
Abstract: This paper introduces the Peregrine breather solution of the nonlinear Schrödinger-type equation as an innovative design wave. The major benefits are the potential to generate abnormal waves of certain frequency up to physically possible wave heights, the symmetrical abnormal wave shape and the availability of an analytical solution. The characteristics of Peregrine breathers as well as their impact on marine structures were investigated. To evaluate the applicability of the Peregrine breather solution as design wave, wave-structure investigations with a LNG carrier were performed in a set of Peregrine breathers at certain frequencies. The investigations comprised model tests as well as numerical simulations. For the purpose of comparison, a real-world abnormal wave reproduction was additionally investigated allowing the evaluation of breather-type abnormal waves regarding the applicability as design wave. Therefore, the famous 'New Year Wave', an abnormal wave recorded in the North Sea at the Draupner jacket platform on January 1st, 1995, was selected. Highlights: We introduce Peregrine breather as design wave for wave-structure investigation. We compare the characteristics of Peregrine breather with real world abnormal waves. We show that Peregrine breather can be used for generating tailored extreme waves. We show that the impact of Peregrine breather causes extreme ship response. We show that the breather solution is applicable for numerical simulations.